LET-dependent radiosensitization effects of gold nanoparticles for proton irradiation. (3rd October 2016) - Li, Sha; Penninckx, Sébastien; Karmani, Linda; Heuskin, Anne-Catherine; Watillon, Kassandra; Marega, Riccardo; Zola, Jerome; Corvaglia, Valentina; Genard, Geraldine; Gallez, Bernard; Feron, Olivier; Martinive, Philippe; et al.
Abstract: The development of new modalities and protocols is of major interest to improve the outcome of cancer treatment. Given the appealing physical properties of protons and the emerging evidence of biological relevance of the use of gold nanoparticles (GNPs), the radiosensitization effects of GNPs (5 or 10 nm) have been investigated in vitro in combination with a proton beam of different linear energy transfer (LET). After the incubation with GNPs for 24 h, nanoparticles were observed in the cytoplasm of A431 cells exposed to 10 nm GNPs, and in the cytoplasm as well as the nucleus of cells exposed to 5 nm GNPs. Cell uptake of 0.05 mg ml −1 of GNPs led to 0.78 pg Au/cell and 0.30 pg Au/cell after 24 h incubation for 10 and 5 nm GNPs respectively. A marked radiosensitization effect of GNPs was observed with 25 keV μ m −1 protons, but not with 10 keV μ m −1 protons. This effect was more pronounced for 10 nm GNPs than for 5 nm GNPs. By using a radical scavenger, a major role of reactive oxygen species in the amplification of the death of irradiated cell was identified. All together, these results open up novel perspectives for using high-Z metallic NPs in protontherapy.